Saudi Arabia and aerospace medicine in the era of the national vision of 2030 - Shirah, Bader H.; Al Talhi, Yousef M. (International Journal of Health Sciences, 2019)
The interest of Saudi Arabia in space was clear with the recent establishment of the Saudi Space Commission (SSC) on December 27, 2018, and the appointment of his royal highness Prince Sultan bin Salman (the first Saudi astronaut) as the chairman of the board of directors. The recent inauguration of SSC is an opportunity for Saudi Arabia to be a major contributor in the field of aerospace medicine, which can be achieved through a variety of endeavours. There are several limitations for Saudi Arabia to contribute in the field of aerospace medicine such as the absence of previous experience in the field and the lack of trained individuals. This article is considered a call for action and serves as the initial step for the dawn of the field of aerospace medicine in Saudi Arabia. Aerospace medicine should be a priority in the SSC national strategy, which is currently under construction.